A fully absorbable biomimetic polymeric micelle loaded with cisplatin as drug carrier for cancer therapy. Issue 1 (19th April 2017) - Zhuang, Weihua; Ma, Boxuan; Liu, Gongyan; Chen, Xiaobing; Wang, Yunbing
Abstract: cis-dichlorodiammineplatinum(II) (CDDP)-loaded polymeric micelles for cancer therapy have been developed to reduce the serious side effects of cisplatin CDDP. Herein, polymeric micelles incorporated with cisplatin are prepared based on the complexation between CDDP and hydrophilic poly (L -glutamic acid)-b-poly (2-methacryloyloxyethyl phosphorylcholine) (PLG-b-PMPC) diblock copolymers. These CDDP-loaded micelles possess an average size of 91 nm with narrow distribution, providing remarkable stability in media containing proteins. The release of CDDP from the micelles is faster at pH 5.0 and pH 6.0 than that at pH 7.4 and in a sustained manner without initial burst release. In addition, there is almost no difference in cellular uptake between these CDDP-loaded micelles and free CDDP. Moreover, in vitro cytotoxicity test shows they possess high efficacy to kill 4T1 cells as compared with free drug. Thus, PLG-b-PMPC copolymer might be a promising carrier for CDDP incorporating in cancer therapy.